TINGKAT TUNTUTAN KERJA ANALISIS HUBUNGAN , KOMPETENSI SDM DAN MANAJEMEN PROYEK TERHADAP KUALITAS, BIAYA DAN WAKTU PENYELESAIAN PROYEK: STUDI KASUS DI PT LEN INDUSTRI (Persero) - , Widyo Isworo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the relationship between the project performance, which compossed of quality, cost and time, and the exogenous constructs that influence which consist of the level of work demands, competence and project management in PT Len Industri (Persero). As the object of this study are employees of PT Len Industri (Persero) that have been involved in the project. Data from object study was obtained by deffuse research questionnaire to the object study. Of the 110 questionnaires sent to the object of study there are 90 questionnaires returned and eventually obtained 81 questionnaires that deserve to be analyzed. The collected data was analysed using a statistical method Partial Least Square (PLS). The results showed that the level of work demands in a positive affect on the cost and duration time of completion of the project, but had no effect on the quality of project completion. HR competency level of the project positively affected the quality of project completion, but no effect on the time and cost of the project completion. While project management is found in this study a positive effect on the quality and negatively affect the duration project completion time, but had no effect on the cost of project completion.